2020
DOI: 10.9734/ejmp/2020/v31i1130295
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antioxidant Potential of Aqueous Extracts of Millettia laurenti, Lophira alata and Milicia excelsa, Commonly Used in the Cameroonian Pharmacopoeia

Abstract: Aims: As the world nowadays is turning towards the research of biologically active natural compounds, this work aimed at assessing the antioxidant potential of compounds contained in the aqueous extracts of three common Cameroonian pharmacopoeia plants, namely Millettia laurenti (Wengé) seeds, Lophira alata (Azobé) leaves and Milicia excelsa (Iroko) barks and the associated bioactive compounds. Methodology: After being dried and ground, they were macerated in water and the polyphenols, tannins, flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…We also found a good correlation between the levels of bioactive contents (polyphenols, flavonoids, alkaloids and tannins), the scavenging and reducing power antioxidant assays at R 2 = 0.95. These results corroborated the study of Edoun et al, [14] and Konczak et al, in [16], who found respective correlation coefficients of 0.94 and 0.8315 for native Cameroonian and Australian herbs and spices. Fruits are very good sources of antioxidants and have many different antioxidant components.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found a good correlation between the levels of bioactive contents (polyphenols, flavonoids, alkaloids and tannins), the scavenging and reducing power antioxidant assays at R 2 = 0.95. These results corroborated the study of Edoun et al, [14] and Konczak et al, in [16], who found respective correlation coefficients of 0.94 and 0.8315 for native Cameroonian and Australian herbs and spices. Fruits are very good sources of antioxidants and have many different antioxidant components.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the selectivity of suitable solvents and extraction methods is important due to the various composition of phytochemicals. Most studies have demonstrated that methanol and ethanol solvents can extract more bioactive compounds in plants [14,15]. The differences between extraction methods (extraction conditions and extraction concentrations) not only influence the bioactive compound contents of extracts, but also affect their antioxidant potential.…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be explained by the fact that organic solvent like methanol and ethanol can easily pass through the cell membrane and extracted insoluble secondary metabolites present in the plants like flavonoids, tannins, terpenoids, phenolic compounds and alkaloids which are potentially endowed with antibacterial properties ( Onivogui et al., 2015 ; Al Farraj et al., 2020 ). In previous studies carried out on M. laurentii seeds and L. alata leaves, it was demonstrated that these plants contained high amounts of flavonoids, polyphenols, tannins and alkaloids ( Edoun et al., 2020 ). The difference of concentration of these compounds varying with the solvent ( Nair et al., 2006 ) may therefore explain the different antibacterial activity observed later.…”
Section: Discussionmentioning
confidence: 99%
“…The vegetal materials used in this study were M. laurentii seeds and L. alata leaves. These plants were chosen because they are popular plants used in traditional medicine as judged by local healers and also because studies carried out on these plants (phytochemical screening) revealed their high contents in bioactive compounds such as polyphenols, tannins, flavonoids and alkaloids (Edoun et al, 2020). The plants were collected in April 2019 in the forest zone of the National School of Water and Forests of Mbalmayo (3 31 0 00 00 N and 11 30 0 00 E), Centre Region of Cameroon.…”
Section: Vegetal Materialsmentioning
confidence: 99%
“…However, its remarkable resistance to decay, particularly in marine environments, justifies the extra effort required [ 10 ]. Studies have reported that L. alata contains a rich variety of extractives, including polyphenols, tannins, flavonoids, alkaloids, and other compounds [ 11 , 12 ]. Notably, extracts derived from L. alata have demonstrated antibacterial effects and possess significant medicinal value [ 13 ].…”
Section: Introductionmentioning
confidence: 99%